The Effect of Applying Drill Method on In Teaching Students’ Writing Ability - Harahap, Fitri Rahmadani (The Explora, 2021)
This research was aimed to develops teaching writing by using drill method as method in teaching writing descriptive paragraph. This study was conducted applying Nana Sudjana (1989:86) theory. The research took place at MTs.Swasta IRA Medan. The sample consisted of class VII. The instruments employed in this study experimental research which consist of pre-test and post-test.. The findings of the study were the quality of the developed technique as media viewed from theexperts is very good (88 %). Most students gave positive responses. Most students said that the method was interesting and it could help them to write descriptive texts easily. The results of the test show that the method improved their ability in writing descriptive paragraph (average score: 80, 12).The scoring system was based on five aspects; namely content, organization, vocabulary, language use, mechanics. Therefore, the writer suggests that English teachers develop method as one of the creative way to improve the students’ ability in writing descriptive texts.